Paulina Rivoli – Moniuszko’s heroines and a Falcon soprano? - Winiszewska, Hanna (Interdisciplinary Studies in Musicology, 2023)
Paulina Rivoli was the first Warsaw Halka and then the first Countess in Moniuszko’s operas. In this article, I will relate how the singer, who at first frowned on Moniuszko’s proposals, launched the performance tradition of two great Moniuszko operas in which she created the title roles. Her immediate successors had to deal with the inevitable comparisons. Unfortunately, Rivoli suffered from serious vocal complaints. This was nothing unusual: phoniatric disorders plagued singers throughout Europe at that time, when massive changes were occurring in the aesthetics of solo singing. Rivoli was excellent in bel canto repertoire – a style of singing favourable to a maturing voice, which allowed her to develop fully. What was Halka’s original singing style? That was probably a mature period for Rivoli’s voice, which did not necessarily correspond to the notion of a modern, very ‘light’, even Donizettian approach to singing this role. Some of the circumstances surrounding the twilight of Rivoli’s career allow us to draw a comparison between her and another great singer whose career ended prematurely. Cornélie Falcon famously sang the role of Rachel in Halévy’s La Juive, which contributed to her legendary demise, and she had lost her voice irrevocably five years after her debut. Rivoli and Falcon sang similar repertoire, including Alice in Meyerbeer’s Robert le diable (Falcon’s debut and an early role for Rivoli), Donna Anna in Mozart’s Don Giovanni and Valentine in Les Huguenots, but Rivoli’s downfall was spread over a longer period, as her career lasted more than 20 years. Nor was her loss of voice as drastic as that of Falcon, who was literally left voiceless during a performance of Niedermeyer’s Stradella. Rivoli’s problems grew gradually, peaking after the premiere of The Countess [Hrabina]. It was probably this last burst of energy that ultimately depleted her powers altogether. Paulina Rivoli, Halka, The Countess, Stanisław Moniuszko, singers, singing, history of singing, Falcon soprano, vocal problems, voicelessness